Differences between male and female referees in adjudicating male soccer matches - Zuo, Y.; Liu, X.; Sun, F.; Yang, Y.; Tong, Y. (Journal of Human Sport & Exercise, 2025)
Referees play important roles in the soccer matches, i.e., adjudicating the outcome of the soccer match and the players` performance. Female referees were included into male soccer matches and received a lot of attention recently. Although female referees were suggested to be less competent than male referees and also suffered from discrimination, few studies have not directly compared the female and male referees in adjudicating the male soccer matches. In this study, the data from the last five seasons of Maurice Revello Tournament Cup matches were compared to see whether referee gender differences were exited in adjudicating the players` performance in the tournament. The hypothesize is there were no difference between different genders referees in adjudicating matches. Data from 109 matches (52 with female referee and 57 with male referee) from the 2018 to 2024 seasons were selected and divided them into two groups based on different referee genders. All variables (scores, shots, shots on target, passes, fouls, penalties, yellow cards, red cards, offsides, and corners) were analysed using independent samples t-tests and generalized linear models. The results showed there were no significant difference in all variables (scores, p = .94, shots p = .076, passes p = .729, fouls p = .541, offsides p = .249) between matches adjudicated by female and male referees. The findings indicated that female referees were not weaker than male referees in adjudicating the male soccer matches. It can break the gender prejudges bias and discrimination against female referees and encourage more women to join as soccer referee and adjudicate in male soccer matches.